AKTIVITAS ANTIMIKROBA EKSTRAK DIETIL ETER KARANG LUNAK Sinularia sp. TERHADAP BEBERAPA MIKROBA UJI SECARA KLT- BIOAUTOGRAFI - Rachmat Kosman (As-Syifaa Jurnal Farmasi, 2010)
An antimicrobial assay has been done to Sinularia sp.  The preliminary research has done screening toward extract of ethanol, diethyl ether, and n-butanol concentration 1 mg/ml using 9 trial microbe. The result has been showed that diethyl ether extract actively to inhibiting growth of Pseudomonas aeruginosa, Salmonella thypi, and Streptococcus mutans. The antimicrobial activity assay toward diethyl ether extract of Sinilaria sp. is carried out by liquid dilution methode to find the Minimum Inhibitory Concentration (MIC) value by concentration 0,025%, 0,05%, 0,1%, 0,2%, 0,4%, and 0,8%. Experiment  has been continued by into solidified medium to decide the Minimum Lethality Concentration (MLC). The result showed that MIC could not  be determined due to turbidity of test solution, mean while the MLC toward Pseudomonas aeruginosa, Salmonella thypi, and Streptococcus mutans each of them 0,2%, 0,8%, and 0,8%. To identify the group of the compound in diethyl ether extract which gave antimicrobial activity by TLC-Bioautography test. Then obtained  best result from separation of compound by TLC  which using eluent combination n-Hexan : etil asetat (6 : 4). The result of TLC-Bioautography test showed that growth of Pseudomonas aeruginosa can inhibited by spot at the rate of flow (Rf) 0,9 , of Salmonella thypi can inhibited by spot at the rate of flow (Rf) 0,9 and 0,56 and then of Streptococcus mutans can inhibited by spot at the  rate of flow (Rf) 0,24. Result of identifying of chemical compound indicated that the active compound give the positive for steroid at Rf 0,9, Rf 0,24 and Rf 0,56.Key Words : Antimikroba, Sinularia sp, KLT-Bioautografi